A strain gauge analysis of microstrain induced by various splinting methods and acrylic resin types for implant impressions - Cerqueira, Nunes M.; Özcan, Mutlu; Gonçalves, Marianna; Da Rocha, Daniel M.; Vasconcellos, Diego K.; Bottino, Marco A. [UNESP]; Yener-Salihoğlu, Esra (My University, 2012)
The aim of this study was to investigate the level of microstrain that is exerted during polymerization of acrylic resins used for splinting during implant impressions. Material and Methods: Two acrylic resins (GC Pattern Resin, Duralay II) and square transfer coping splinting methods were evaluated by means of strain gauge analysis. Two implants were embedded in a polyurethane block, and the abutments were positioned. Sixty specimens were prepared using two square transfer copings that were rigidly connected to each other using the acrylic resins. The specimens were randomly divided into three groups of 20 each for the splinting methods: Method 1 was a one-piece method; in method 2, the splint was separated and reconnected after 17 minutes; and in method 3, the splint was separated and reconnected after 24 hours. In each group, half the specimens were splinted with GC Pattern Resin and the other half were splinted with Duralay II. Three microstrain measurements were performed by four strain gauges placed on the upper surface of the polyurethane blocks at 5 hours after resin polymerization for all groups. The data were analyzed statistically. Results: Both resin type and splinting method significantly affected microstrain. Interaction terms were also significant. Method 1 in combination with Duralay II produced significantly higher microstrain (1,962.1 µe) than the other methods with this material (method 2: 241.1 µe; method 3: 181.5 µe). No significant difference was found between splinting methods in combination with GC Pattern Resin (method 1: 173.8 µe; method 2: 112.6 µe; method 3: 105.4 µe). Conclusions: Because of the high microstrain generated, Duralay II should not be used for one-piece acrylic resin splinting, and separation and reconnection are suggested. For GC Pattern Resin, variations in splinting methods did not significantly affect the microstrain created. © 2012 by Quintessence Publishing Co Inc.
Keywords: Acrylic resin; Microstrain; Osseointegrated implants; Splinting techniques; Strain gauge